Oil prices and inflation forecasts - Constantin Bürgi; Prachi Srivastava; Karl Whelan (University College Dublin, UCD School of Economics, 2023)
We examine how people's forecasts for oil or gasoline prices influence their forecasts for broader inflation. We find little evidence from two US household surveys that people over-react to their beliefs about gasoline prices when formulating their forecasts about inflation, with much of the evidence pointing towards under-reaction. We also show that the participants in the ECB's Survey of Professional Forecasters and the Wall Street Journal survey of economists appear to place too little weight on their subjective forecasts for oil prices when making their forecasts for total inflation.
Keywords: E31; E52; D84; Q47; 330; Inflationserwartung; Verbraucher; Wirtschaftsprognose; Ölpreis; Benzinpreis; USA